What Makes Us Human?: The Lutheran Anthropological Link Between Wingren and Ricoeur - Uggla, Bengt Kristensson (Open theology, 2018)
This paper explores the link between the extra nos in Gustaf Wingren’s theological anthropology and the homo capax in Paul Ricoeur’s philosophical anthropology, considered as two creative receptions of the tradition from Luther. I will argue that the reason that we find such synergies between these two thinkers, even though neither of them ever referred to the other, has to do with their common roots in, and their contributions to rethink, the tradition from the Reformation. Wingren takes his specific place in twentieth century theology as an angry critic of the dominant anti-liberal movements that took the distinctively Christian-in opposition to what we all share as human beings-as methodological startingpoint when understanding the Christian faith, and as an alternative he developed understanding of what it means to be human by starting "outside" oneself. Ricoeur’s philosophical position is developed as a creative alternative to both humanist and anti-humanist approaches, expressed as a wounded cogito capable of imagining "onself as another." Taken together, these two thinkers provide us with a profound dialectical way of thinking what it means to be human by bringing together a de-centered self and a centered self as integral parts of a wider dialectics.